Nano Clinoptilolite: Highly Efficient Catalyst for the Synthesis of Chromene Derivatives Under Solvent-Free Conditions - Hallajian, Sara; A. Khalilzadeh, Mohammad; Tajbakhsh, Mahgol; Alipour, Eskandar; Safaei, Zahra (Combinatorial Chemistry & High Throughput Screening, 2015)
An efficient and selective synthesis of substituted chromene derivatives via threecomponent reaction of 4-hydroxycoumarin or 1,3-dicarbonyl compounds, activated acetylenic compounds and N-nucleophiles is described. The reaction was conducted under solvent-free conditions at 70°C using potassium fluoride impregnated on natural zeolite as a cheap and available solid base. The procedure has several advantages involving selectivity, excellent yields and a convenient work-up method.
Keywords: 4-hydroxycoumarin